Pengaruh Kompetensi dan Kompensasi terhadap Kinerja Melalui Motivasi (pada Guru PAUD di Kecamatan Kertasari Kabupaten Bandung) - Rahmatika, Ike; Maddinsyah, Ali (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of Competence and Compensation on Performance through Motivation among Early Childhood Education (PAUD) Teachers in Kertasari District, Bandung Regency. In this research, the author used quantitative research with a survey method. A total of 133 teachers were selected as respondents through a proportionate stratified random sampling technique. Data were analyzed using Path Analysis. The results of the study are as follows: 1) Competence and Compensation significantly influence Motivation simultaneously. 2) Competence significantly influences Motivation partially. 3) Compensation significantly influences Motivation partially. 4) Motivation significantly influences Performance. 5) Competence and Compensation simultaneously influence Performance through Motivation. 6) Competence partially influences Performance through Motivation. 7) Compensation partially influences Performance through Motivation.